บ้านวังถั่ว : ภูมิปัญญาที่กำลังจะสูญหาย - ศรีรักษา, กิตติสันต์ (Journal of Fine and Applied Arts Khon Kaen University, 2015)
A study of pottery production of Wang Tua Village, Wang Chai Sub-district, Nam Phong District, Khon Kaen Province. The tools used in this research and the field research are non-participated observation, non-structured interview with people in the community which includes the local potters, entrepreneurs and villagers to learn about history of the community, culture and their way of life which passing through generations to be called the local wisdom. This community has an interesting geography which has enough raw materials for the production of traditional pottery, or the Earthenware and this local wisdom process is still remaining from the past year through present time in order to response to human use. The result from this research shows that the community is still holding on to the traditional form and process for producing pottery, it is an earthenware pottery without glazing, the form of pottery similar to the pottery excavated at the Archaeological Non Chai.†The pottery process is currently changing into an interesting direction, in the case of the traditional production which is the local wisdom. Although the progress in science and technology will facilitate to ease of the process of pottery production, but most of the local potters in the community are still remaining their traditional process. Therefore depending on the technologies without considering to the other important factors might not be the conclusion of local wisdom to exist sustainably.